Aloe-emodin mediates the inhibitory effect of LncRNA D63785 on the PI3K/Akt/mTOR pathway in nasopharyngeal carcinoma - He, Min; Xie, Lei; Huang, Jiayi; Su, Han; Hu, Jiahua; Xie, Liuping; Li, Mengqin; Zeng, Xin; Tang, Jianhong (Frontiers in Pharmacology, 2025)
BackgroundLong non-coding RNAs (lncRNAs) are dysregulated in nasopharyngeal carcinoma (NPC), yet their interplay with pharmacological agents like aloe-emodin (AE) remains unclear. This study explores AE’s anti-NPC mechanisms via lncRNA D63785 and the PI3K/Akt/mTOR pathway.MethodsNPC cells (CNE1, C666-1) were treated with AE, followed by qRT-PCR and Western blotting to assess lncRNA D63785 and PI3K/Akt/mTOR pathway proteins. siRNA-mediated lncRNA D63785 knockdown combined with functional assays (CCK-8, EdU, colony/wound-healing) evaluated AE’s effects on proliferation, migration, and pathway activity. In vivo validation used nude mouse xenografts.ResultsLncRNA D63785 was overexpressed in NPC cells (p < 0.01). AE suppressed lncRNA D63785 expression, concurrently reducing PI3K/Akt/mTOR phosphorylation (p < 0.05). siRNA knockdown partially reversed AE’s inhibition of NPC cell viability, proliferation, and migration. In vivo, AE attenuated tumor growth (p < 0.05), correlating with lncRNA D63785 downregulation and PI3K/Akt/mTOR dephosphorylation.ConclusionAE exerts anti-NPC effects by targeting the lncRNA D63785-PI3K/Akt/mTOR axis, offering a novel therapeutic strategy. These findings bridge AE’s pharmacological activity with lncRNA regulatory networks in NPC pathogenesis.